FROM FINANCIAL LITERACY TO BUSINESS PERFORMANCE: STRUCTURAL EQUATION EVIDENCE FROM URBAN MSMES IN A DEVELOPING ECONOMY - Hanu, La; AS, Mansur; Ahsan, Jabal; Subaedah, Sitti; Baharuddin, Baharuddin (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) make an important contribution to employment and local economic activity, yet growth in the number of businesses does not always translate into better, more sustainable performance. Financial literacy is often discussed as one factor behind this problem, although previous studies have commonly focused on financial knowledge and behavior or relied on descriptive and conventional statistical approaches. Evidence from urban MSMEs in developing economies is also less extensive, particularly when financial literacy and business performance are examined as latent constructs. This study examines the effect of financial literacy on MSME performance using a quantitative explanatory design. Primary data were obtained from 225 MSME owners through a structured questionnaire and analyzed using Structural Equation Modeling (SEM). The results show that 43.3% of respondents have a low level of financial literacy and 36.4% are in the moderate category. The structural model further indicates a positive and statistically significant relationship between financial literacy and MSME performance (p < 0.05). This study extends earlier work by examining financial literacy as an internal business capability and testing its relationship with performance through a structural modeling approach in an urban developing-economy setting. The findings suggest that MSME development programs should not focus solely on access to capital. Practical support in financial recording, budgeting, cash-flow management, and the use of formal financial services is also needed to strengthen business capability and support more sustainable performance.